2000
DOI: 10.1177/109634800002400210
|View full text |Cite
|
Sign up to set email alerts
|

Using Consumer Behavior Research to Understand the Baby Boomer Tourist

Abstract: This article focuses on consumer behavior research to better understand Australian baby boomer tourists, although the principles and methods behind this empirical study are equally applicable to the baby boomer tourism markets in the United States, Canada, and New Zealand, all of which experienced a major postwar baby boom. Lifestyle research, using both secondary and primary data, was the principal behavioral research approach enhanced with survey findings on the psychological motivation for vacation travel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…According to Roy Morgan Research (2005), the baby boomer traveller cohort accounted for up to 40% (664 000) of total Australian travellers in the Asia-Pacific region (January-December 2005), spending $AUD4.1 billion. This figure is considerably higher than the one-third estimate by Cleaver et al (2000). Although many of the baby boomer travellers in the Roy Morgan report were found to be budget-conscious, 21% spent $AUD200-$299 per person per day and 22% spent $AUD300.…”
Section: Baby Boomer Travellersmentioning
confidence: 73%
See 1 more Smart Citation
“…According to Roy Morgan Research (2005), the baby boomer traveller cohort accounted for up to 40% (664 000) of total Australian travellers in the Asia-Pacific region (January-December 2005), spending $AUD4.1 billion. This figure is considerably higher than the one-third estimate by Cleaver et al (2000). Although many of the baby boomer travellers in the Roy Morgan report were found to be budget-conscious, 21% spent $AUD200-$299 per person per day and 22% spent $AUD300.…”
Section: Baby Boomer Travellersmentioning
confidence: 73%
“…Three participants considered that VFR travel could counterbalance the growing age demographics of baby boomer air travellers. Whilst VFR travel was identified by Cleaver et al (2000), Glover and Prideaux (2010) and Xinran et al (2001) as bearing some importance to baby boomer air travellers, there was no discussion in regard to the economic benefits to the airlines of this type of travel.…”
Section: (Vi) Natural Population Growthmentioning
confidence: 99%
“…Previous research identified that the 30-55 age group was an important segment to target for tourism products (Cleaver et al, 2000). In addition, the over 55 consumer group represents one of the largest populations in the travel industry (Malley, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…the study adopted a push motivation perspective by using a shortened version of the leisure Motivation Scale put forward by Beard and ragheb (1983). the scale has been used in many leisure contexts, successfully employed across a wide range of sociodemographic groups and applied to culturally diverse samples (e.g., Ashton-Shaeffer & Constant, 2006;Cleaver, green, & Muller, 2000;Correia, Silva, & Moço, 2008;Mohsin, 2008;Mohsin & ryan, 2007;Perrett, 2007;ryan & gledon, 1998). Another important strength, which is particularly important in the context of this study, is that the scale has proved to be successful in identifying types or clusters of leisure travelers (ryan & gledon, 1998).…”
Section: Choice Of Segmentation Basismentioning
confidence: 99%